Functional limitations and educational needs among children and adolescents with heart disease. (22nd July 2018) - Farr, Sherry L.; Downing, Karrie F.; Riehle‐Colarusso, Tiffany; Abarbanell, Ginnie
Abstract: Objective: To examine how cognitive and motor limitations in children with heart disease are associated with education and participation in extracurricular activities. Design: Using 2009–2010 parent‐reported data from the National Survey of Children with Special Health Care Needs (NS‐CSHCN), we examined prevalence of five functional limitations (learning/concentration, communication, self‐care, gross motor skills, and fine motor skills) by diagnosed heart disease status using chi‐square tests and multivariable logistic regression. Among CSHCN with heart disease, we examined the associations between severity of each functional limitation and missing ≥11 days of school in the past year, receiving special education services, and interference with extracurricular activities. Results: CSHCN with heart disease (n = 1, 416), compared to CSHCN without (n = 28, 385), more commonly had "a lot" of difficulty in the five functional areas ( P < .01; adjusted odds ratios: 1.8‐3.3). Among CSHCN with heart disease, "a lot" of difficulty with learning/concentration was most common (35%), followed by communication (21%), self‐care (14%), gross motor skills (12%), and fine motor skills (10%). Among CSHCN with heart disease, compared to those without, respectively, 27% and 15% missed ≥11 days of school, 45% and 29% received special education services, and 49% and 29% experienced interference with extracurricular activities ( P < .01 for all). Level of difficulty with the five functional areas was associated with receipt of special education services and participation in extracurricular activities ( P < .001). Conclusion: These results support the American Heart Association recommendations to screen children with congenital heart disease for age‐appropriate development and provide services when needed.